Monitoring Covid-19 Policy Interventions - Paolo Giudici; Emanuela Raffinetti (Frontiers Media S.A., 2020)
A very key point in the process of the Covid-19 contagion control is the introduction of effective policy measures, whose results have to be continuously monitored through accurate statistical analysis. To this aim we propose an innovative statistical tool, based on the Gini-Lorenz concentration approach, which can reveal how well a country is doing in reducing the growth of contagion, and its speed.